Experimental and theoretical investigation of aqueous and methanolic extracts of Prunus dulcis peels as green corrosion inhibitors of mild steel in aggressive chloride media - Pal S.; Lgaz H.; Tiwari P.; Chung I.-M.; Ji G.; Prakash R. (My University, 2025)
Prunus dulcis (almond) is one of the most commonly ingested dry fruits by peoples in their routine diet plan due to its high nutrition content. However, almond peels are not eaten and thrown as a waste material. The reason is that the peels are not easily digested in human body due to its low solubility in aqueous medium. Also, the peels contain low amount of cyanides. Surprisingly, almond peels also contain various active bio-compounds which have not been explored properly for any industrial purpose. With the idea of utilizing a waste material and checking solution dependability, the aqueous and methanolic extracts of almond peels have been prepared and investigated by experimental techniques and theoretical tools. The protection efficiency of the extracts in reduction of mild steel (MS) dissolution in 0.1 M HCl has been determined by electrochemical methods (impedance analysis and polarization behavior). The results shows that methanolic and aqueous extracts avert 93% and 85% mild steel loss respectively, which portray that methanolic extract is more effective than aqueous extract. This fact is supported by the surface analysis of mild steel samples done by HRSEM and AFM. UV–vis and FTIR spectroscopy analysis reveals the reason that methanol can extract more phytochemcial constituents of almond peels than water. The free energies of adsorption (ΔG°) for both extract's molecules have been determined based on adsorption coefficient (Kads) obtained from Langmuir isotherm fitting of inhibition data, which suggest that adsorption is neither pure physical nor pure chemical, i.e., mixed type. DFT modeling and Monte carlo simulation techniques are also explored to investigate theoretical adsorption and inhibition characteristics of the molecules, which supports the interpretation of the experimental results. © 2018 Elsevier B.V.